2000
DOI: 10.1017/s0142716400004021
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual is as bilingual does: Metalinguistic abilities of Arabic-speaking children

Abstract: The study explores the effects of the relationship between exposure to two languages in childhood and metalinguistic abilities. Arabic-speaking children who had been exposed to both spoken and literary Arabic were compared to Russian–Hebrew bilinguals and Hebrew monolinguals. All of the children were in kindergarten or first grade. The tests included language arbitrariness, phonological awareness, and vocabulary. As compared to the Hebrew monolinguals, the Russian–Hebrew bilinguals revealed the following patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 19 publications
2
90
0
9
Order By: Relevance
“…In another experiment, which focused on children, Bialystok (1988) found that bilingual children were more willing to accept the possibility of switching the names of the sun and the moon and were more able to play along with the switching game than monolingual children. Similar evidence of an increased ability to recognize the arbitrariness of a name has been found in bilingual children by others as well (Cummins, 1978;Edwards and Christopherson, 1988;Eviatar and Ibrahim, 2000;Feldmen and Shen, 1971).…”
Section: Cognitive Effects Of Bilingualismsupporting
confidence: 80%
See 1 more Smart Citation
“…In another experiment, which focused on children, Bialystok (1988) found that bilingual children were more willing to accept the possibility of switching the names of the sun and the moon and were more able to play along with the switching game than monolingual children. Similar evidence of an increased ability to recognize the arbitrariness of a name has been found in bilingual children by others as well (Cummins, 1978;Edwards and Christopherson, 1988;Eviatar and Ibrahim, 2000;Feldmen and Shen, 1971).…”
Section: Cognitive Effects Of Bilingualismsupporting
confidence: 80%
“…Recently this area of research has received much attention in the fields of Second Language Acquisition (SLA) and Bilingualism. The results continue to be varied, however, as many studies have found positive cognitive effects for bilinguals, especially in the areas of control processes (Bialystok, 2005) and the ability to distinguish meaning and form (Bialystok, 1988;Cummins, 1978;Edwards and Christopherson, 1988;Eviatar and Ibrahim, 2000;Feldmen and Shen, 1971). One proposal for understanding this varied evidence is Cummins' Threshold Theory (Cummins, 1976), which posits that the effects of bilingualism on cognitive abilities is dependent on proficiency in the two languages.…”
Section: Introductionmentioning
confidence: 99%
“…Literary Arabic (Fusha, and its current uses called Modern Standard Arabic-MSA) is used by educated people in literature, news (both written and oral) and intellectual conversations. To some extent, children entering the first grade who encounter literary Arabic for the first time can find it to be almost a foreign language (Abu-Rabia 2002;Abu-Rabia et al, 2003;Eviatar & Ibrahim, 2001;Ibrahim & Aharon-Peretz, 2005;Saiegh-Haddadd, 2003). Exposure to literary Arabic prior to the first grade assists children in learning how to read and write (Abu-Rabia, 2002), sharing a limited subgroup of words, the two forms of Arabic sematically, phonologically and syntactically are different.…”
Section: Characteristics Of the Arabic Languagementioning
confidence: 99%
“…In previous study, we have shown that children exposed to both forms of Arabic function as bilinguals, as they show higher levels of phonological awareness than age matched monolingual Hebrew speakers (Eviatar & Ibrahim, 2001). This would predict that they should show an advantage in reading acquisition.…”
Section: Reading In Arabic and Hebrewmentioning
confidence: 89%
“…2) This is an extremely important research in the light of the findings of Ibrahim et al (2007) regarding differences in reading speed in Arabic and Hebrew among Arabic and Hebrew speakers (Ibrahim, Eviatar, & Aharon-Peretz, 2007). Ibrahim et al (2007) examined the utilization of the good phonological awareness among children Arabic mother tongue speakers compared to uni-lingual speakers of other languages (Hebrew speakers) and bi-lingual speakers (Hebrew and Russian speakers) (Eviatar & Ibrahim, 2001). They found that in reading, Arabic speakers do not utilize this advantage and that their performance in their language (Arabic) is lower (in terms of reading time and accuracy) than other lingual groups.…”
Section: Transfer Of Skills From One Language To the Othermentioning
confidence: 99%